THE INFLUENCE OF MINERAL FERTILIZERS ON WATER CONSUMPTION AND PRODUCTIVITY OF WINTER WHEAT - Hanhur, V. V.; Kocherha А. А.; Pypko О. S.; Kabak, Y. I.; Len, O. I. (Scientific Progress & Innovations, 2020)
The priority task of the agro-industrial complex of Ukraine is increasing the manufacturing of grain products with improved quality indicators for ensuring food security of the state and exports to foreign markets. The decisive role in solving this problem belongs to winter wheat (Triticum aestivum L.), as a leading food grain crop. The aim of the research was to determine the effect of different rates of mineral fertilizers, differentiated application of nitrogen on water consumption of winter wheat plantings and the level of grain productivity. During the research the following scientific methods were used: analysis, synthesis, field, and statistical. The results of the conducted studies show that different doses of mineral fertilizers and differentiated nitrogen application, as a significant factor influencing the activity of growth processes, led to an increase in tillering rate by 14.6–34.7 %, plant height 2.9–8.7 %, the number of grains in the spike by 1.8– 10.1 %, as compared with the variant without fertilization. It has been found that mineral fertilizers increase the effectiveness of using available soil moisture for the formation of winter wheat yield, in particular, total water consumption made 539–579 m3/t, which was 46–86 m3/t or 7.4–13.8 % less than in the control. The tendency was registered for more rational using moisture to form a yield unit of the main product in case of transferring part of nitrogen from basic application to early spring fertilization. It has been found that due to applying mineral fertilizers in the technology of winter wheat cultivation, a significant increase in grain yield is achieved in comparison with the variant without fertilizers. The value of additional wheat grain yield on experimental plots was 0.45–0.92 t/ha or 8.8–17.7 % relative to the control. The best conditions of mineral fertilization, which ensured the maximum winter wheat yield of 6.11 t/ha were registered under applying fertilizers at the rate of N80P90K50 + N30. A steady tendency to increasing winter wheat productivity under applying fertilizers’ mineral nitrogen in different periods was observed.